Strain Rate Effect on Shear Strength of Rounded and Angular Sand - Basudhar P.K.; Acharya I.P.; Anubhav (My University, 2025)
The paper is mainly focused on the strain rate effect on shear strength of sands in direct shear test. Experimental investigations on two sands, one with rounded smooth grains (Ennore standard sand) and another with angular grains (Ganga sand), were carried out with a view to investigate the difference in shear strength of the sands at different shear strain rates. From the test results, it was found out that friction angle depends largely on gradation and particle angularity. Angular well-graded particles give the highest friction angle, and the rounded uniform particles give the least. Angle of shearing resistance increases with increasing the strain rate. For these two sands, relationships have also been established for prediction of peak friction angle as a function of relative density and rate of shearing strain. © 2020, Springer Nature Singapore Pte Ltd.